2020
DOI: 10.3390/su12103966
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous Knowledge and Learning Capability: The Magic Potion for Employee Creativity and Sustainable Innovation Performance

Abstract: This paper studies the effect that ambidextrous knowledge, i.e., oriented knowledge within a firm towards the development of exploitation activities and oriented knowledge towards the development of exploration activities, has on employee creativity, research and development, and sustainable product innovation. We contend that both tacit and explicit knowledge affect employee creativity, research and development, and sustainable product innovation. We empirically tested our hypotheses by using multisource data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 121 publications
(175 reference statements)
1
12
0
Order By: Relevance
“…Based on this, it seems that bank that does not have the potential and actual capacity to formulate codified strategies against environmental change due to strategic incompatibility, face more damage from human resource performance management. The result obtained by the research studies of Muñoz-Pascual and Galende (2020), Mom et al (2019), Stark and Poppler (2017) and Khalil Nezhad et al (2020) correspond. Based on the results obtained, it is suggested that banking system, given the existing limitations in the field of environmental instability, should strengthen their strategic capacities with other bank based on strategic models such as consortium to create effective knowledge to promote human resource development.…”
Section: Discussionsupporting
confidence: 53%
“…Based on this, it seems that bank that does not have the potential and actual capacity to formulate codified strategies against environmental change due to strategic incompatibility, face more damage from human resource performance management. The result obtained by the research studies of Muñoz-Pascual and Galende (2020), Mom et al (2019), Stark and Poppler (2017) and Khalil Nezhad et al (2020) correspond. Based on the results obtained, it is suggested that banking system, given the existing limitations in the field of environmental instability, should strengthen their strategic capacities with other bank based on strategic models such as consortium to create effective knowledge to promote human resource development.…”
Section: Discussionsupporting
confidence: 53%
“…A clear example today is the development of the vaccine against Covid-19. Innovation is currently being developed in SMEs around the world with knowledge, motivation, and relationship of all employees [120][121][122][123]. Faced with the current economic and health crisis caused by Covid-19, companies are using their highest levels of innovation and HR to adapt and develop new materials and medical devices in record time, achieving compatibility through the invisible hand of their own legitimate economic interests with the enormous social interests that this field of work entails.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…On the contrary, companies with insufficient absorption capacity have poor response and utilization ability to the environmental conditions of the host country [ 82 ], and are unable to effectively identify and utilize the technological environment and institutional environment of the host country. Secondly, knowledge is the most important resource for product innovation performance, and acquiring new external knowledge is particularly difficult [ 83 ]. R&D internationalization enterprises with strong absorptive capacity can realize the gaps in the technology field more quickly and integrate the new external knowledge acquired.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%